INTEGRATING FLOOD RISK INTO URBAN PLANNING IN INDONESIA - Novid Gumelar (FAKULTAS TEKNNIK UNIVERSITAS SWADAYA GUNUNG JATI, 2020)
Flood is the disaster with the highest frequency occurrence in the world resulted in the greatest loss of both material and nonmaterial. This loss is exacerbated by the incidence of floods that occur in urban areas that have large population and asset values. Efforts to reduce the risk of urban flood disaster have been done, but this effort is still sectoral. This article examines how flood risks are integrated into urban spatial planning in Indonesia. The integration of floods in Indonesia is carried out with an environmental assessment approach in the development plan, with a Strategic Environmental Assessment/SEA (KLHS) attached to each development plan.